Investigation and Analysis of Bridge Pot Bearing - S, Priyadarshika; M, Rajkannan (International Research Journal of Multidisciplinary Technovation, 2019)
The paper present describes the investigation and analysis of bridge pot bearing. A technical solution to the problem of unavoidable movements in bridge structures is the use of bridge bearing. The road engineering consists of three major structure, road embankments, bridges, and tunnels. In consideration of the cost of land acquisition in urban areas, the trend of road engineering migrating to hilly or mountain areas has been developed. Pot bearing has many advantages the extremely long service year in addition to the correct installation the routine inspection and maintained of pot bearing in the service time are necessary for them to fully function. Current domestic research mainly concentrates of rubber bearing and has only few discussion and analysis on pot bearing.